2004
DOI: 10.1124/dmd.104.001487
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Inhibitory Effects of Nitric Oxide on Cytochrome P450-Mediated Drug Metabolism: Time Dependency and Reversibility Profiles in Isolated Perfused Rat Livers

Abstract: ABSTRACT:Nitric oxide (NO) is implicated as a mediator in the decreased catalytic activities of cytochrome P450 (P450) enzymes during inflammation or infection. Here, we examined the time course and the reversibility of the NO effect on P450s using isolated perfused rat livers. Livers were perfused at a constant rate with the NO donor sodium nitroprusside (SNP) for 0.5 or 1 h, followed by washout periods of 0 to 2.5 h. At the end of perfusion, microsomes were prepared and analyzed for P450 activities and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…Supporting the above findings, very recently (Vuppugalla and Mehvar, 2004a), we showed the inhibitory effects of NO on P450 to be rapid, concentration-dependent, and enzyme-selective in an isolated perfused rat liver (IPRL) model. Furthermore, we also conducted time course studies to assess the mechanisms responsible for the NO-mediated P450 inhibition and demonstrated that the short-term inhibitory effects of NO are time-dependent, consisting of both reversible and irreversible components (Vuppugalla and Mehvar, 2004b).One of the novel findings of our IPRL studies (Vuppugalla and Mehvar, 2004a,b) was the apparent lack of effect of NO donors on CYP2D1 enzyme, along with different degrees and time courses of inhibition or reversal of activities for other P450 enzymes. These studies were carried out only with a single substrate concentration.…”
mentioning
confidence: 99%
“…Supporting the above findings, very recently (Vuppugalla and Mehvar, 2004a), we showed the inhibitory effects of NO on P450 to be rapid, concentration-dependent, and enzyme-selective in an isolated perfused rat liver (IPRL) model. Furthermore, we also conducted time course studies to assess the mechanisms responsible for the NO-mediated P450 inhibition and demonstrated that the short-term inhibitory effects of NO are time-dependent, consisting of both reversible and irreversible components (Vuppugalla and Mehvar, 2004b).One of the novel findings of our IPRL studies (Vuppugalla and Mehvar, 2004a,b) was the apparent lack of effect of NO donors on CYP2D1 enzyme, along with different degrees and time courses of inhibition or reversal of activities for other P450 enzymes. These studies were carried out only with a single substrate concentration.…”
mentioning
confidence: 99%
“…The NO-induced decrease in glucuronide formation (Fig. 5) may be because reduction in the activity of UDPGT resulted from an interaction of NO with the critical thiol-containing amino acid residues of the enzyme, similar to that reported between the P450 apoprotein and NO (Minamiyama et al, 1997;Vuppugalla and Mehvar, 2004b). In addition to the decrease in the formation of DOR and HOM glucuronides (Fig.…”
Section: Effects Of Snp or Isdn On The Recovery Of Dem And Its Metabomentioning
confidence: 48%
“…The differential effects of NO on the V max values of these enzymes may be because of differences between the two enzymes in the accessibility of heme and/or cysteine thiolate residues to NO (Gergel et al, 1997). Additionally, because NO reacts with thiol groups of amino acid residues in the apoprotein (Minamiyama et al, 1997;Vuppugalla and Mehvar, 2004b), it may affect the binding of substrates to these enzymes and therefore impact their K m values, selectively. This is because the degree of involvement of the thiolcontaining cysteine residues in the substrate binding may be different for various P450 enzymes (Vuppugalla and Mehvar, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations